GEOMAGNETIC CONJUGACY OF MODERN TECTONIC STRUCTURES - G. Ya. Khachikyan; N. S. Zhakupov; N. Zh. Kadyrkhanova (Геодинамика и тектонофизика)
An earthquake is an element of the global electric circuit (GEC) –  this new idea suggested in the space age is tested in our study. In the frame of the GEC concept, one may expect that tectonic structures of the northern and southern hemispheres may be magnetically conjugated. It is found that the midocean ridges of the southern hemisphere, located along the boundary of the Antarctic lithosphere plate, are magnetically conjugated with the areas of the junction of continental orogens and platforms in the northern hemisphere. The closest geomagnetic conjugacy exists between the southern boundary of Nazca lithospheric plate and the northern boundaries of Cocos and Caribbean lithospheric plates.